2009
DOI: 10.1186/1471-2164-10-6
|View full text |Cite
|
Sign up to set email alerts
|

The iron/heme regulated genes of Haemophilus influenzae: Comparative transcriptional profiling as a tool to define the species core modulon

Abstract: Background: Haemophilus influenzae requires heme for aerobic growth and possesses multiple mechanisms to obtain this essential nutrient. Although an understanding of the heme acquisition mechanisms of H. influenzae is emerging, significant gaps in our knowledge remain. Unresolved issues include the identities of all genes exhibiting altered transcription in response to iron and heme availability, the fraction of such genes functioning in iron/heme acquisition, and the heterogeneity of this gene set among clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 70 publications
1
67
0
Order By: Relevance
“…These observations indicated that changes in gene transcription were due to the loss of Fur and that the identified genes are indeed Fur regulated. Finally, we compared our microarray data to previously published data that monitored transcriptional responses of three Haemophilus strains following transition from heme-depleted to heme-replete medium ( Table 2, the NTHi, type b, and Rd columns) (53). There was a strong correlation between changes in gene expression due to the loss of Fur in strain 86-028NP with quantitation of changes in gene expression due to an increase in available iron and heme, an in vitro analog for increased repression of gene expression by Fur (53).…”
Section: Characterization Of Fur In Nthi Strain 86-028npmentioning
confidence: 99%
“…These observations indicated that changes in gene transcription were due to the loss of Fur and that the identified genes are indeed Fur regulated. Finally, we compared our microarray data to previously published data that monitored transcriptional responses of three Haemophilus strains following transition from heme-depleted to heme-replete medium ( Table 2, the NTHi, type b, and Rd columns) (53). There was a strong correlation between changes in gene expression due to the loss of Fur in strain 86-028NP with quantitation of changes in gene expression due to an increase in available iron and heme, an in vitro analog for increased repression of gene expression by Fur (53).…”
Section: Characterization Of Fur In Nthi Strain 86-028npmentioning
confidence: 99%
“…Recently, global analyses of iron-and/or Fur-responsive transcriptomes of diverse bacterial pathogens, such as H. pylori, Pseudomonas syringae, Vibrio cholerae, Yersinia pestis, Haemophilus influenzae, S. enterica serovar Typhimurium, and Listeria monocytogenes, have revealed a number of novel regulatory roles for Fur (12,20,40,56,68,94,101,102,107). First, Fur has been demonstrated to repress transcription even in the absence of iron, a process termed apo-Fur regulation (13) (Fig.…”
Section: Fur Functions As a Global Regulatory Proteinmentioning
confidence: 99%
“…2C). Transcriptome analysis has also identified additional genes that are activated by iron-bound Fur (12,56,68,101,102,107).…”
Section: Fur Functions As a Global Regulatory Proteinmentioning
confidence: 99%
“…Nontypeable H. influenzae are no exception, and have a variable number of systems to scavenge iron and heme from many different host sources, including transferrin, hemoglobin, heme, heme:hemopexin, heme:albumin, hemoglobin:haptoglobin complexes, and siderophores produced by other microorganisms (Morton et al, 2010; Whitby et al, 2009). A number of these systems have been implicated in Hi virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hemR was more common among invasive Hib isolates (97.4%) than among commensal NTHi isolates (86.9%), with a prevalence ratio of 1.15 (p=0.0169). Whitby et al used microarray and qPCR analyses to demonstrate that expression of hemR was increased under iron/heme limiting conditions in OM NTHi strain R2866, capsule deficient type d strain Rd, and invasive Hib strain 10810 (Whitby et al, 2009). …”
Section: Introductionmentioning
confidence: 99%